Bartholomew and the oobleck - Seuss, Dr (Random House, 1977)
The King, tired of rain, snow, sun, and fog, commands his magicians to make something else come out of the sky, but when oobleck falls in sticky, greenish droplets, Bartholomew Cubbins shames the King and saves the Kingdom.